2020
DOI: 10.37934/arfmts.76.3.111
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Optimum Thickness of Glass Wool Roof Thermal Insulation Performance

Abstract: Countries in south east Asia are mostly experiencing tropical climate conditions. Therefore, the use of the air conditioning has been increased to reduce the tension and achieve thermal comfort inside the buildings. In order to reduce the energy consumption, thermal insulation has been introduced to lower down the indoor temperature. The main objective of this study is to determine the optimum thickness of the glass wool insulation. To conduct the study, a wooden room model is built based on the classroom that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…These investigations examined the thermal comfort of classrooms in temperate climates such as the UK, Denmark, and the Netherlands [15][16][17]; Mediterranean climates such as those in Italy, Portugal, and Cyprus [2,6,18,19] and subtropical climates such as those in Taiwan, Australia, and China [20,21]. Over this decade, several studies in naturally ventilated classrooms in the tropics have also been conducted [7,20,[22][23][24][25][26][27]. These investigations demonstrated that students quickly adapted to naturally ventilated classes and found comfort levels between 24 and 31 degrees Celsius [5].…”
Section: Introductionmentioning
confidence: 99%
“…These investigations examined the thermal comfort of classrooms in temperate climates such as the UK, Denmark, and the Netherlands [15][16][17]; Mediterranean climates such as those in Italy, Portugal, and Cyprus [2,6,18,19] and subtropical climates such as those in Taiwan, Australia, and China [20,21]. Over this decade, several studies in naturally ventilated classrooms in the tropics have also been conducted [7,20,[22][23][24][25][26][27]. These investigations demonstrated that students quickly adapted to naturally ventilated classes and found comfort levels between 24 and 31 degrees Celsius [5].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the combination of the stone wool and radiant barrier was able to reduce the attic temperature to as low as 30 • C when the insulations are installed directly below the cement roof tiles. Muhieldeen et al [22] examined the optimum thickness of glass wool as the roof insulation to reduce indoor air temperature and heat flux transmission. The results showed that the glass wool thickness of 25 mm, 50 mm, and 75 mm managed to lower the indoor air temperature by 1.0 • C, 1.3 • C, and 1.5 • C, and heat flux transmission by 3%, 12%, and 20%, respectively.…”
Section: Previous Workmentioning
confidence: 99%
“…Muhieldeen et al, [11] evaluated the temperature variation inside a test room for several forms of thermal insulation, such as polyethylene, expanded polystyrene, and rock wool. The results showed that 5.2 cm of rock wool insulation offered the best temperature reduction inside the test room, at 3.85%, followed by 2.3 cm of expanded polystyrene and 0.5 cm of polyethylene insulation, with interior temperature reductions of 2.49% and 0.89% respectively.…”
Section: Introductionmentioning
confidence: 99%